La terminación convencional del procedimiento sancionador: la administración concertada en materia sancionadora - Morón Urbina, Juan Carlos (2016)
One of the most important transformations of contemporary Administrative Law Penalties is the one related to the openness to cooperation with private actors, considering that one of its expressions is the commitment to cease.In this academic paper, the author realizes a theoretical approach on the legal concept of concerted administration regarding penalties, and analyzes its regulation within sectoral rules. Finally, he offers some criticisms of the use of this concept by the public administration.